Causal links to missed Australian midwifery care: What is the evidence? - Blackman, Ian; Hadjigeorgiou, Eleni; McNeill, Liz (My University, 2020)
INTRODUCTION The incidences and types of missed nursing care in the acute care and community sectors are both ubiquitous and quantifiable, however, there are few research studies relating to the type and frequency of missed maternity-based care for mothers and families. The aim of this study is to estimate the incidences and types of Australian missed midwifery care and to identify those factors that have causal links to it. METHODS A non-experimental, descriptive method using a Likert developed MISSCARE scale was used to ascertain consensus estimates made by Australian midwives. Electronic invitations were extended to their membership using an inclusive link to the MISSCARE survey. Inclusion criteria were all ANMF members who were midwives and currently employed within the Australian public and private healthcare systems. Data analysis was undertaken using both Rasch analysis and Structural Equation Modelling. RESULTS The type and frequency of missed Australian midwifery care can be quantified and several demographic factors are significant predictor variables for overall missed midwifery care. The most prevalent aspects of missed care in the Australian midwifery setting are midwives’ hand hygiene, supportive care, perinatal education, and surveillance type midwifery practices. CONCLUSIONS As the frequencies and types of missed midwifery care in Australia have been identified, it is possible for midwives to be mindful of minimising care omissions related to hand hygiene, providing supportive care and education to mothers as well as surveillance-type midwifery practices.
Keywords: Australia; Missed midwifery care; Modelling